NGOs and social protection: The Philippine experience - Largoza, Gerardo L. (Animo Repository, 2004)
Assessing the contribution of NGOs to social protection in the Philippines means having to draw the distinction between their service delivery activities and advocacy activities. There is a evidence that NGOs have had a beneficial impact on local communities despite having to deal with a number of obstacles, in particular, the limited short-term funding available and the dependence on external donors. However, such benefits tend to be limited to the kind that moves individuals from being very poor to being only marginally poor. More comprehensive structural reforms in income distribution and public good provision need to be implemented in order to maximise the gains from any NGO-government partnership. This is, unfortunately, where possible internal contradictions arise, especially for NGOs that derive their mandate from international conventions that are on a collision course with the government's neo-liberal agenda. We argue that the 'Philippine experience' may consist of NGO over time becoming the basis of more programmatic political parties.